2021
DOI: 10.1101/2021.02.02.429315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perturbations in 3D genome organization can promote acquired drug resistance

Abstract: Acquired drug resistance is a major problem in the treatment of cancer. hTERT-immortalized, untransformed RPE-1 (RPE) cells can acquire resistance to taxol by derepressing the ABCB1 gene, encoding for the multidrug transporter P-gP. Here we have investigated how the ABCB1 gene is derepressed. We show that activation of the ABCB1 gene is associated with reduced DNA methylation, reduced H3K9 trimethylation and increased H3K27 acetylation at the ABCB1 promoter. In addition, we find that the ABCB1 locus has moved … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…We have previously shown that in human retinal pigment ephitilial‐1 (RPE‐1), a major mechanism of Taxol resistance is transcriptional activation of the ABCB1 gene, that encodes for the multidrug resistance protein MDR1 or P‐Glycoprotein (PgP) (Tame et al , 2017; preprint: Manjón et al , 2021). Using the lentiviral system LentiGuide‐Puro from the Zhang Lab (Sanjana et al , 2014a), we cloned different sgRNAs targeting different noncoding regions across the ABCB1 locus to induce a DSB (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that in human retinal pigment ephitilial‐1 (RPE‐1), a major mechanism of Taxol resistance is transcriptional activation of the ABCB1 gene, that encodes for the multidrug resistance protein MDR1 or P‐Glycoprotein (PgP) (Tame et al , 2017; preprint: Manjón et al , 2021). Using the lentiviral system LentiGuide‐Puro from the Zhang Lab (Sanjana et al , 2014a), we cloned different sgRNAs targeting different noncoding regions across the ABCB1 locus to induce a DSB (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We next decided to compare the chromatin landscape of the ABCB1 promoter in RPE‐1 parental cells and the Taxol‐resistant clones with the LentiGuide‐Puro integration. It is known that in RPE‐1 parental cells, ABCB1 is found in a repressive chromatin environment, consequently leading to transcriptional repression (preprint: Manjón et al , 2021). We therefore performed chromatin immunoprecipitation followed by massive parallel sequencing (ChIP‐seq) for the repressive histone modification H3K9me3.…”
Section: Resultsmentioning
confidence: 99%
“…This compartment switch would then result in the switching of neighboring genes, which may increase their probability of later becoming activated as well. Recent work has shown that spatial reorganization of a chromosome region can make it more permissive for de-repression, even if the structural switch does not immediately change its expression level ( Manjón et al, 2021 Preprint ). Is it possible that earlier transcriptional events required for the cell to survive a particular insult trigger a full compartment shift?…”
Section: Discussionmentioning
confidence: 99%
“…This compartment switch would then result in the switching of neighboring genes, which may increase their probability of later becoming activated as well. Recent work has shown that spatial reorganization of a chromosome region can make it more permissive for derepression, even if the structural switch does not immediately change its expression level (Manjón et al, 2021) . Is it possible that earlier transcriptional events required for the cell to survive a particular insult trigger a full compartment shift?…”
Section: Discussionmentioning
confidence: 99%